PEMBELAJARAN BERPIKIR KRITIS: MAKNA DAN RELEVANSINYA BAGI MAHASISWA DI PERGURUAN TINGGI - URA WERUIN, URBANUS (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2025)
This literary study article discusses the relevance, challenges, obstacles, and methods that can be used in critical thinking learning for students in higher education. With critical thinking learning, students are not only able to remember and memorize various ideas, opinions, concepts, or theories but also able to understand, sort, analyze, evaluate, and synthesize various ideas, opinions, or theories critically and rationally in the presence of healthy reason. Critical thinking is nothing more than thinking about how people should think. Critical thinking skills are related to the ability to understand, sort, analyze, and synthesize various ideas, information, or problems faced in order to make decisions quickly, accurately, effectively, and efficiently. The absence of adequate training, limited knowledge and literature, time constraints, and preconceptions that are difficult to change can be obstacles in themselves in learning critical thinking. Critical thinking learning can begin with understanding the problem; formulating the problem; applying logical reasoning; and applying deductive-inductive thinking to draw the right conclusions. Critical thinking knowledge and skills are useful in studying any field; including in solving practical problems in the world of work.